Diversification, ownership structure and firm performance: A South African case study - Chitah, Musonda K (Department of Finance and Tax, 2022)
The purpose of this study is to examine the impact of diversification (both industrial and geographical) on the performance of non-financial South African firms listed on the Johannesburg Stock Exchange (JSE). The study goes further to examine the impact of ownership structure (managerial ownership and ownership concentration) in the context of diversification on firm performance. This is done in an effort to determine if diversification is an effective strategy in enhancing firm performance (which is measured by Tobin's Q) in South African firms. Fixed effect regression analysis is used on a sample of 164 firms during the period 2010 to 2019. For comparison purposes, the study also conducts; ordinary least squares (OLS) and random effect analyses. The study finds that industrial diversification has no significant effect on firm performance, geographical diversification reduces firm performance and overall specialized firms perform better than diversified firms do. These results support the argument that the costs of diversification surpass its benefits. The study also finds that managerial ownership reduces firm performance contradicting the agency theory. Furthermore, ownership concentration has no significant effect on performance of South African firms.